PKM pelatihan pengolahan sosis bergizi - Haerani Haerani; Andi Hudiah; Rika Riwayani (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
Nutrition sausage processing training for housewives on Barrang Lompo island is a partnership program to the community (PKM) as a solution to the problem of the needs of housewives on Barrang Lompo island. The participants of the training were 10 housewives on Barrang Lompo island. The training method is done in the form of lectures, questions and answers, discussions and practice. The PKM program aims to: 1) understand more about the knowledge and benefits of processing nutritious sausages. 2) practice the processing of nutritious sausages properly and correctly. 3) increase motivation to sell with new variants that have never been sold on the island of Barrang Lompo. After conducting the PKM activity Processing of nutritious sausages to housewives on the island of Barrang Lompo, it can be concluded that: A total of 10 participants have understood well how to process fish into nutritious sausages and their benefits for toddlers. Furthermore, as many as 10 participants who were skilled in processing fish into nutritious sausages were also motivated by the importance of empowering housewives through training on sustainable food processing.